Interconnected factors in EFL engagement: classroom climate, growth mindset, and achievement goals - Ma, Weiran; Yang, Weian; Bu, Qinggang (Frontiers in Psychology, 2024)
Introduction This study explores the relationships among classroom climate, growth mindset, achievement goal orientation, and student engagement in the context of English as a foreign language (EFL) education in China. The study aims to understand how these factors interact to influence student engagement and motivation in EFL learning. Methods Data were collected through a questionnaire administered to 587 Chinese undergraduate EFL students. The questionnaire assessed students’ perceptions of classroom climate, growth mindset, achievement goal orientation, and engagement. Structural equation modeling (SEM) was utilized to examine the relationships among these variables. Results The SEM analysis revealed significant positive correlations among classroom climate, growth mindset, achievement goal orientation, and student engagement. Both classroom climate and growth mindset were found to directly and positively predict student engagement. Additionally, achievement goal orientation mediated the relationships between both classroom climate and student engagement, and between growth mindset and student engagement. Discussion The findings underscore the interconnectedness of classroom climate, growth mindset, and achievement goal orientation in shaping student engagement in EFL education. These results suggest that fostering a positive classroom climate and promoting mastery-oriented goals can enhance student motivation and contribute to more effective language acquisition. Practical implications for EFL educators are also discussed.